Organize - Beyes, Timon, 1973-; Rossiter, Ned; Martin, Reinhold, 1964-; Lovink, Geert; Conrad, Lisa, Dr (Book collections on Project MUSE., 2019)
"This book is dedicated to the 'knot' of media and organization. It does not claim to untie the knot, for that would be a grandiloquent, impossible project. But it endeavours to disentangle important threads, both conceptually and empirically (as if the two could be held distinct). In this sense, while each of the following texts can be read independently from the others, they have been developed in joint discussion and are meant to hang together and cohere as a joint response to the question of media as/and organization"--